Rare case of basal cell carcinoma of genital area: Diagnosis and treatment - Thakur, Shabnum; Gupta, Manish; Dhatwalia, Aarti (Indian Journal of Case Reports, 2019)
The most incessant skin malignancy is basal cell carcinoma (BCC), arising from cells of the basal layer of the epithelium or from the external root sheath of the hair follicle. BCC of the genital area is an aberrant subsistence. We are presenting one such rare case of BCC of the genital area which was not amenable to surgery because it was locally advanced disease if it was executed it may have result in highly mutilating surgery. Since the patient refused the main modality, the best available option for her was chemoradiotherapy for averting the post-surgical anatomical disfigurement of the private parts which may results in the psycho-social ordeal to the patient after loss of docility. The rationale of presenting this case is the rarity of BCC in the genital region and it should always kept in mind as a differential diagnosis by physicians, and biopsy from visible lesions is always recommended. Also, the majority of patients are treated with local treatment but in case of locally advanced or non-amenable lesions; induction chemotherapy followed by radiation/ chemoradiation therapy is an option and can be effective.